MINAT BERWIRAUSAHA MELALUI PENGETAHUAN, MOTIVASI DAN SELF EFFICACY DI KALANGAN MILLENIAL - Rina Dewi (Media Mahardhika, 2020)
This purpose of this study wants to know how the influence of knowledge and motivation on intention in entrepreneurship through the capacity of self-efficacy in the millennial generation. The method used in this research is quantitative method of confirmatory factor analysis using a sample of 291 respondents using probability random sampling techniques and using Structural Equation Modeling techniques. The findings are that knowledge and motivation have an effect on self-efficacy which will ultimately shape the intention of the millennial generation to be entrepreneurial. The study reasult can be used the importance of develop the millennial generation for entrepreneurship to reduce unemployment by creating jobs for themselves and the community around their environment so as to achieve economic and social welfare.